Evaluating the Effectiveness of Behavioral Strategies in Mitigating Anxiety and Depression among Medical Students - Shahzadi, Shazia; Juhary, Ali; Munir, Naureen; Shah, Syed Shoaib; Farooque, Muhammad Anees (2024)
Compared to ten years ago, medical college students now face more complicated problems, such as relationship problems that are more serious and mental health difficulties like depression, anxiety, and suicide ideas. Counselling is essential for assisting students in developing a deeper understanding of both themselves and their environment, which will enable them communicate with others more skillfully. The purpose of this study was to evaluate how much counselling assisted medical students in controlling their anxiety and depression. An experimental design of "before-and-after with control" was used. 120 randomly chosen medical students from a private medical college were given the Beck Anxiety and Depression Inventory. The students were divided into two groups, the experimental group and the control group, with 30 males and 30 females in each. Means, standard deviations, t-tests, and one-way ANOVA were used to analyze the data. The study discovered that the students who received counselling had lower levels of anxiety and depression. Counselling proved beneficial in boosting self-confidence and enhancing the ability to adjust, by reducing anxiety and depression among medical students. Both male and female students in the experimental group showed significant reductions in anxiety and depression levels, while the control group, which did not receive counselling, maintained the same levels of anxiety and depression.